PENGARUH ATRIBUT PERGURUAN TINGGI TERHADAP KEPUASAN MEMILIH PERGURUAN TINGGI - Irfandi Buamonabot; Nurlaila Nurlaila; Nurdin Nurdin (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
Education plays an important role in the development of a nation. In addition, education is also an important instrument in ensuring the sustainability of individuals and society. Thus, it can be ascertained that education has an advanced control whether or not a nation. The purpose of this study was to examine the effect of college attributes on the satisfaction of choosing a college. The sampling technique that is Purposive sampling was chosen based on the consideration that students who were sampled were students who had registered, so that the sample size used in this study were 85 respondents. The respondents in this study were students of the Faculty of Economics and Business, Khairun University. 85 respondents were collected from the survey. Data analysis uses simple regression. The results of the study showed that the college attributes had an effect on the satisfaction of choosing a college. The results of this study are also consistent with the opinion of Oliver (1997) that satisfaction is the customer's response to the fulfillment of their needs. That means assessing that a form of privilege of an item or service or goods / service itself, provides a level of comfort associated with fulfilling a need including meeting needs under expectations or meeting needs exceeding expectations.